1992
DOI: 10.1021/j100191a056
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-proton coupling in the NMR spectrum of benzene on an alumina-supported platinum catalyst

Abstract: The homonuclear decoupled proton NMR spectrum of benzene associatively chemisorbed on a 5.0% wt/wt Pt/A1203 catalyst is reported. The structure of the resonance is attributable to heteronuclear dipolar or pseudodipolar couplings to platinum-195 nuclei in the surface of the particle. Comparison of simulated spectra for benzene molecules in various sites coupled by the heteronuclear dipolar interaction to an array of platinum atoms indicates that only benzene in the "on top" geometry is consistent with the obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…In contrast, Tirendi et al [120] used nuclear magnetic resonance and suggested that Bz molecules are located at the atop site. Inferred from the orientations of the STM images, Weiss and Eigler [121] reported the coexistence of Bz molecules at both the hcp and fcc sites.…”
Section: Previous Studiesmentioning
confidence: 98%
“…In contrast, Tirendi et al [120] used nuclear magnetic resonance and suggested that Bz molecules are located at the atop site. Inferred from the orientations of the STM images, Weiss and Eigler [121] reported the coexistence of Bz molecules at both the hcp and fcc sites.…”
Section: Previous Studiesmentioning
confidence: 98%
“…Adsorbed PF 3 on a number of qt metal surfaces is known from ESDIAD measurements to have a bound (hindered) to free rotor transition as the temperature is increased [30][31][32]. Jn NMR experiments, benzene has been shown to rotate on Ft particles which are predominantly textured Pt4 111) [33,34]. STM images of azulene have been interpreted as rapidly rotating molecules [35].…”
Section: Linear Acstm Spwcroscopymentioning
confidence: 99%
“…in CO on transition metals. [26][27][28] On the other hand, several studies [29][30][31][32][33][34] have shown that for carbon not directly bonded to the metal, e.g. separated by a heteroatom such as S 30 or physisorbed, [32][33][34] the change in peak position is more moderate, < 20 ppm, and can be used to monitor adsorption.…”
mentioning
confidence: 99%
“…[26][27][28] On the other hand, several studies [29][30][31][32][33][34] have shown that for carbon not directly bonded to the metal, e.g. separated by a heteroatom such as S 30 or physisorbed, [32][33][34] the change in peak position is more moderate, < 20 ppm, and can be used to monitor adsorption. [29][30][31][32][33][34] One recent study demonstrated that the chemical shift of formate on different metal nanoparticles correlated well with the calculated dband center, formate decomposition rate, metal work function, and specific activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation